2022
DOI: 10.2147/ott.s341120
|View full text |Cite
|
Sign up to set email alerts
|

Selinexor, Bortezomib and Dexamethasone: An Effective Salvage Regimen for Heavily Pretreated Myeloma Patients

Abstract: Multiple myeloma (MM) patients with triple-and penta-refractory disease have a poor survival and limited treatment options. Selinexor, in combination with bortezomib and dexamethasone, demonstrated clinical activity in the STOMP study as well as in the BOSTON study in previously treated patients with disease refractory to a proteasome inhibitor (PI). Patients and Methods: Here, we report a real-world case series of 7 heavily pretreated MM patients who had been extensively pretreated with bortezomib and had dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition to the STOMP study (Table 3) [62], selinexor‐Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77, 78]. Reflecting the efficacy seen with selinexor‐dexamethasone in this later‐relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Clinical Studies Of Selinexor In Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the STOMP study (Table 3) [62], selinexor‐Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77, 78]. Reflecting the efficacy seen with selinexor‐dexamethasone in this later‐relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Clinical Studies Of Selinexor In Multiple Myelomamentioning
confidence: 99%
“…or standard-risk cytogenetics, the benefit of selinexor-Vd versus Vd was maintained in terms of ORR (high-risk 79% vs. 58%; standard-risk 75% vs. 65%) and PFS (high-risk: median 12.9 vs. 8.6 months, HR 0.73; standard-risk: median 16.6 vs. 9.5 months, HR 0.61), albeit that there was evidence of the poor prognostic impact of high-risk cytogenetics on outcomes in both arms [63] In addition to the STOMP study (Table 3) [62], selinexor-Vd has been investigated in two studies of heavily pretreated patients with RRMM (Table 4) [77,78]. Reflecting the efficacy seen with selinexordexamethasone in this later-relapse setting, both studies showed notable response rates, with three of the 10 patients across the studies achieving ≥VGPR.…”
Section: Selinexor-based Triplet Regimens For Rrmmmentioning
confidence: 99%
“…Management algorithms suggest considering selinexor in heavily pretreated MM patients as an alternative to BCL-2 inhibitor venetoclax, immunotherapy or CAR-T cell therapies [30]. In December 2020, selinexor was approved by the FDA in combination with bortezomib and dexamethasone for patients who have undergone one prior therapy only [31].…”
Section: Selinexor In R/r MMmentioning
confidence: 99%
“…Selinexor is a promising agent already registered for the second or further line therapy of R/R MM [31] and in the third or further line therapy of DLBCL NOS [50]. The drug has already been and is still being assessed in numerous clinical and preclinical studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%